The Lymphocytic Choriomeningitis Virus Matrix Protein PPXY Late Domain Drives the Production of Defective Interfering Particles. - Christopher M Ziegler; Philip Eisenhauer; Emily A Bruce; Marion E Weir; Benjamin R King; Joseph P Klaus; Dimitry N Krementsov; David J Shirley; Bryan A Ballif; Jason Botten (PLoS Pathogens, 2016)
Arenaviruses cause severe diseases in humans but establish asymptomatic, lifelong infections in rodent reservoirs. Persistently-infected rodents harbor high levels of defective interfering (DI) particles, which are thought to be important for establishing persistence and mitigating virus-induced cytopathic effect. Little is known about what drives the production of DI particles. We show that neither the PPXY late domain encoded within the lymphocytic choriomeningitis virus (LCMV) matrix protein nor a functional endosomal sorting complex transport (ESCRT) pathway is absolutely required for the generation of standard infectious virus particles. In contrast, DI particle release critically requires the PPXY late domain and is ESCRT-dependent. Additionally, the terminal tyrosine in the PPXY motif is reversibly phosphorylated and our findings indicate that this posttranslational modification may regulate DI particle formation. Thus we have uncovered a new role for the PPXY late domain and a possible mechanism for its regulation.